2019
DOI: 10.1093/bioinformatics/btz514
|View full text |Cite
|
Sign up to set email alerts
|

Genetic cooperativity in multi-layer networks implicates cell survival and senescence in the striatum of Huntington’s disease mice synchronous to symptoms

Abstract: Motivation Huntington’s disease (HD) may evolve through gene deregulation. However, the impact of gene deregulation on the dynamics of genetic cooperativity in HD remains poorly understood. Here, we built a multi-layer network model of temporal dynamics of genetic cooperativity in the brain of HD knock-in mice (allelic series of Hdh mice). To enhance biological precision and gene prioritization, we integrated three complementary families of source networks, all inferred from the same RNA-seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Interestingly, biological content analysis (see Materials and methods), including KEGG pathway and gene ontology (GO) analysis, revealed that, in addition to implicating the ‘HD pathway’ (in interneurons, astrocytes) and pathways involved in neuronal activity (e.g., ‘Wnt signaling’ and ‘cAMP signaling’ in Drd2 -MSNs), GDS clusters implicate stress response pathways in all cell types ( Supplementary file 2 ). Noticeably, cluster centroid Drd2-1 ( Drd2 -MSNs: cluster centroid 1, down-regulation across CAG repeats) implicates stress response and cell survival genes such as Hipk4 , a kinase that promotes HD pathogenesis in transgenic flies ( Al-Ramahi et al, 2018 ), and Arpp21 , a cAMP-regulated phosphoprotein that protects neurons against HD pathogenesis in transgenic Caenorhabditis elegans nematodes ( Bigan et al, 2020 ). Using weighted-edge network analysis of the whole-striatum time-series RNA-seq data, we previously found that these two genes belong to a dynamic network that implicates cell survival and cellular senescence and that forms in the striatum of Hdh mice as they become highly symptomatic on a behavioral level (i.e., gene nodes come together into short-path interactions at 10 months of age; Bigan et al, 2020 ), which, as defined herein, may primarily occur in Drd2 -MSNs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, biological content analysis (see Materials and methods), including KEGG pathway and gene ontology (GO) analysis, revealed that, in addition to implicating the ‘HD pathway’ (in interneurons, astrocytes) and pathways involved in neuronal activity (e.g., ‘Wnt signaling’ and ‘cAMP signaling’ in Drd2 -MSNs), GDS clusters implicate stress response pathways in all cell types ( Supplementary file 2 ). Noticeably, cluster centroid Drd2-1 ( Drd2 -MSNs: cluster centroid 1, down-regulation across CAG repeats) implicates stress response and cell survival genes such as Hipk4 , a kinase that promotes HD pathogenesis in transgenic flies ( Al-Ramahi et al, 2018 ), and Arpp21 , a cAMP-regulated phosphoprotein that protects neurons against HD pathogenesis in transgenic Caenorhabditis elegans nematodes ( Bigan et al, 2020 ). Using weighted-edge network analysis of the whole-striatum time-series RNA-seq data, we previously found that these two genes belong to a dynamic network that implicates cell survival and cellular senescence and that forms in the striatum of Hdh mice as they become highly symptomatic on a behavioral level (i.e., gene nodes come together into short-path interactions at 10 months of age; Bigan et al, 2020 ), which, as defined herein, may primarily occur in Drd2 -MSNs.…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, cluster centroid Drd2-1 ( Drd2 -MSNs: cluster centroid 1, down-regulation across CAG repeats) implicates stress response and cell survival genes such as Hipk4 , a kinase that promotes HD pathogenesis in transgenic flies ( Al-Ramahi et al, 2018 ), and Arpp21 , a cAMP-regulated phosphoprotein that protects neurons against HD pathogenesis in transgenic Caenorhabditis elegans nematodes ( Bigan et al, 2020 ). Using weighted-edge network analysis of the whole-striatum time-series RNA-seq data, we previously found that these two genes belong to a dynamic network that implicates cell survival and cellular senescence and that forms in the striatum of Hdh mice as they become highly symptomatic on a behavioral level (i.e., gene nodes come together into short-path interactions at 10 months of age; Bigan et al, 2020 ), which, as defined herein, may primarily occur in Drd2 -MSNs. Cluster centroids Drd2-5 (up-regulation), Drd1-6 (up-regulation), Drd1-8 (down-regulation), Interneurons-0 (down-regulation), Interneurons-4, and Astrocytes-4 (up-regulation) implicate ‘DNA repair’ or ‘DNA damage response’, suggesting that DNA repair is a biological process that is significantly altered in HD models in all four cell types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium voltage-gated channel beta subunit 4 (SCN4B), one of the beta subunits of the sodium channel, regulates the channel gated dynamics and causes voltage-dependent negative shifts in the activation of some α-sodium channels [43] . The variants in SCN4B have been shown to be associated with ventricular tachyacrdia [44] , Huntington's disease [45] , and can be a new biomarker of aggressive cancers [45] . Moreover, Marin et al showed that SCN4B has a very high interconnection and participation in febrile seizures,nervous disorders, neuromuscular and neurodegenerative diseases, and neurobehavioral manifestations [47] .…”
Section: Discussionmentioning
confidence: 99%
“…As we argued above, systematic, automated validation of models is a critical prerequisite of collaborative model development. Accordingly, the BSP includes a software framework for quantitative model validation and testing that explicitly supports applying a given validation test to different models and storing the results [59]. The framework consists of a web service, and a set of test suites, which are Python modules based on the SciUnit package.…”
Section: Integration Of Hippounit Into the Validation Framework And The Brain Simulation Platform Of The Human Brain Projectmentioning
confidence: 99%